¿Por qué es importante participar en las elecciones de un juez de paz no letrado?: el perfil socio-judicial - Castañeda Méndez, Juan Alberto (2022)
The present research work seeks to provide good reasons for the recognition and importance of citizen participation in the electoral process of non-lawyer justices of the peace, based on the idea of the historical constitutional support of justice of the peace, the social concept of justice of the peace from the profile of a socio-judicial judge and electoral aspects of participation and guarantee of the process through the procedural nullity.The main conclusion is that there is a real need to recognize justice of the peace as a backbone issue in society and support for the judicial system itself through the good results of justice of the peace and the expectation of the local population to recognize justice as an element of their rights and duties, so that the realization of democratic elections of justices of the peace is important for an institutional vision of decentralized justice throughout the country. A position that strengthens the idea of the Constitutional State of law in its aspect of access to justice as a way to solve and legitimize justice in the daily work of citizens.